Cardiopulmonary exercise testing for detecting pulmonary arterial hypertension in systemic sclerosis - Dumitrescu, Daniel; Nagel, Christian; Grünig, Ekkehard (Heart, 2017)
Objectives Pulmonary arterial hypertension (PAH) is a devastating disease with limited survival and occurs as a frequent complication in patients with systemic sclerosis (SSc). A deﬁnite diagnosis of PAH is obtained by right heart catheterisation (RHC); however, the initial suspicion is raised by non-invasive methods. We assessed the diagnostic accuracy of key parameters derived from cardiopulmonary exercise testing (CPET) for detecting and ruling out SSc-associated PAH. Methods: In a multicentre setting, we prospectively evaluated 173 consecutive patients with SSc without known PAH, but with clinical suspicion of PAH. Each patient underwent CPET and RHC. Results: RHC identiﬁed PAH in 48 patients (27.8%), postcapillary pulmonary hypertension (PH) in 10 patients (5.8%) and ruled out PH in 115 patients (66.5%). CPET parameters correlated signiﬁcantly with pulmonary haemodynamics. PeakVO2 and VE/VCO2 showed highest correlations with pulmonary arterial pressure, transpulmonary pressure gradient and pulmonary vascular resistance. Several parameters showed high sensitivity and speciﬁcity for PAH detection by receiver operating characteristic analysis. However, peakVO2 showed highest diagnostic accuracy (sensitivity 87.5%, speciﬁcity 74.8% at a threshold level of 13.8 mL/min/ kg). A peakVO2 of >18.7 mL/kg/min was reached by 38/ 173 patients (22%) and excluded PAH in our cohort (negative predictive value 1.0). A nadir VE/VCO2 ratio of >45.5 showed a positive predictive value of 1.0. Diagnostic accuracy was highest in patients with low pulmonary arterial wedge pressure (<12 mm Hg). There were no study-related serious adverse events. Conclusions: CPET is a safe and valuable method in the non-invasive detection of SSc-associated PAH. It may be particularly beneﬁcial for reducing unnecessary RHC procedures.
First published January 6, 2017
Gesehen am 27.09.2018